Prevalence and Determinants of Glucose Intolerance in a Northern Nigerian Population - NJBCS, Author (Nigerian Journal of Basic and Clinical Sciences, 2026)
Background:Insulin resistance is a major factor in the pathogenesis of type 2 diabetes mellitus. This study is aimed at determining the prevalence of insulin resistance in a Northern Nigerian population. Other objectives include determining the interrelationship between body mass index (BMI), waist circumference (WC), waist–hip ratio (WHR), insulin resistance, and plasma glucose levels; and establishing whether insulin resistance is a significant determinant of glucose intolerance in the studied population.Materials and Methods:In total, 400 subjects were recruited using cluster sampling from their respective communities after due consent. Relevant biodata were documented and appropriate examinations including anthropometric measurements were carried out. Oral glucose tolerance test was carried out and fasting plasma insulin levels were also measured. Insulin resistance was calculated using homeostatic model assessment of insulin resistance.Results:The prevalence of insulin resistance was 36.6%, whereas that of glucose intolerance (prediabetes 17.2% and diabetes 9.3%) was 26.5%. Logistic regression analysis showed that insulin resistance, BMI, WC, waist–height ratio, and WHR were significant determinants of glucose intolerance.Conclusions:The prevalence of insulin resistance and glucose intolerance were high. Markers of insulin resistance and some key markers of obesity were important determinants of glucose intolerance in this study.